Smart leaders, smarter teams how you and your team get unstuck to get results - Schwarz, Roger M. (Gildan Audio, 2020)
A proven approach for helping leaders and teams work together to achieve better decisions, greater commitment, and stronger results More than ever, effective leadership requires us to work as a team, but 'many leaders struggle to get the results they need.' When stakes are high, you cant get great results by just changing what you do. You also need to change how you think. Organizational psychologist and leadership consultant Roger Schwarz applies his 30+ years of experience working with leadership teams to reveal how leaders can drastically improve results by changing their individual and team mindset. Provides practical guidance to help teams increase decision quality, decrease implementation time, foster innovation, get commitment, reduce costs and increase trust. Outlines 5 core values leadership teams can adopt to exponentially improve results. Author of 'The Skilled Facilitator and The Skilled Facilitator Fieldbook. Get the results you and your team need. Start by applying the practical wisdom of 'Smart Leaders, Smarter Teams.